Lissencephaly caused by a de novo mutation in tubulin TUBA1A: a case report and literature review - Ren, Sijing; Kong, Yu; Liu, Ruihan; Li, Qiubo; Shen, Xuehua; Kong, Qing-Xia (Frontiers in Pediatrics, 2024)
Tubulin plays an essential role in cortical development, and TUBA1A encodes a major neuronal tubulin. Neonatal mutations in TUBA1A are associated with severe brain malformations, and approximately 70% of patients with reported cases of TUBA1A mutations exhibit lissencephaly. We report the case of a one-year-old boy with the TUBA1A nascent mutation c.1204C>T, p.Arg402Cys, resulting in lissencephaly, developmental delay, and seizures, with a brain MRI showing normal cortical formation in the bilateral frontal lobes, smooth temporo-parieto-occipital gyri and shallow sulcus. This case has not been described in any previous report; thus, the present case provides new insights into the broad disease phenotype and diagnosis associated with TUBA1A mutations. In addition, we have summarized the gene mutation sites, neuroradiological findings, and clinical details of cases previously described in the literature and discussed the differences that exist between individual cases of TUBA1A mutations through a longitudinal comparative analysis of similar cases.